FRI0231 Association of systemic sclerosis with pulmonary sarcoidosis in two cases. (1st June 2001) - Szucs, G; Szolnoki, E; Alexa, M; Szegedi, G
Abstract : Background: Objectives: Methods: A 42-year-old man has been followed up due to mediastinal lymphadeopathy and pleural effusion parallel with Raynaud syndrome, sclerodactylia and bibasal pulmonary fibrosis. He was diagnosed as having systemic sclerosis by the clinical symptoms and skin biopsy and sarcoidosis which was confirmed by the biopsy of mediastinal lymph nodes. A 24-year-old woman has been followed up due to sarcoidosis proved by the biopsy of mediastinal lymph nodes, too) for 3 years before the development of the clinical symptoms of systemic sclerosis. Results: In both patients sarcoidosis were successfully treated with corticosteroids (in the second case corticosteroid treatment was completed with cyclophosphamid becasue of fibrotising alveolitis). We analysed the clinical symptoms, organ manifestation, prognosis in both cases together with the examination of cytokine profile (interferon-g, IL-1, IL-2, IL-4, IL-6, TNF-a) of CD4 positive lymphocytes from periferal blood. Conclusion: Our results showed Th1 dominancy in both cases, which may play an important role in the coexistence of sarcoidosis and systemic sclerosis.